Experiential learning: How pedagogy is changing in medical education - Debkumar Pal; Manish Taywade; Kumbha Gopi (Current Medical Issues, 2022)
Kolb's cycle of experiential learning is the new method of pedagogy for medical education. It is helpful in the integration of book knowledge and practical knowledge, which is an essential component in competency-based medical education. Experiential learning is helpful for students and more interesting also for them.